Pengaruh Dimensi Butiran Tongkol Jagung Serta Komposisi Perekat Terhadap Kemampuan Isolasi Panas - Rumagit, Paul M.; Rasuh, Tonny A.; Tulung, Fransiscus J.; Pangow, Tammy T.V.; Wakari, Agnes J.E. (Neolectura, 2024)
The long-term goal of this study is to get results in the form of cheap, effective, natural, and environmentally friendly thermal energy (thermal) insulators to support the concept of a Green and Sustainable Energy System. The specific purpose of this research is to make partition board specimens made of corn cobs (Zea mays L) by using adhesives from natural materials and testing material according to test standards.The research method was carried out through the process of destroying corn cobs, then filtered with M-50, M-80, and M-100 (Mesh) sizes. Mixing adhesive composition 1:2 & 1:4 for Kanji flour and adhesive composition of 1:1.5 & 1:2 with an Epoxy. Then Conductivity Test is carried out on the Test Box with observation time every 2 minutes.The best data were obtained for mixing Kanji glue, on Mesh 100 - (1:2) surface cross-section pressure of 10 kg with conductivity value = 0.01018257 J / ms, and Epoxy Glue mixture, on Mesh 100 - (1:2) surface cross-section pressure 20 kg with Conductivity value = 0.010614466 J / ms.